1086. Epidemiology, Risk Factors, and Effect of Antifungal Prophylaxis on Early Invasive Fungal Infection in Heart Transplant Recipients. (31st December 2020) - Yetmar, Zachary A; Lahr, Brian; Brumble, Lisa; Banacloche, Juan Gea; Steidley, D Eric; Kushwaha, Sudhir; Beam, Elena
Abstract: Background: Invasive fungal infection (IFI) in heart transplant recipients is associated with increased mortality and poor outcome. Reports have estimated the risk of 1-year IFI to be 3.4-8.6% with renal replacement therapy, delayed chest closure, and reoperation suggested as risk factors. However, the role of antifungal prophylaxis is unclear, though previous studies have suggested a reduced incidence of invasive Aspergillosis . The transplant program in Mayo Arizona provides 6 months of universal azole prophylaxis for Coccidioides, while Rochester and Florida only provide prophylaxis to high risk patients. We sought to define epidemiology and risk factors for 1-year IFI and determine the effect of antifungal prophylaxis. Methods: We conducted a retrospective cohort study of patients undergoing single-organ heart transplantation at Mayo Rochester, Florida, or Arizona from January 2000 to March 2019. We identified baseline characteristics, details of transplant hospitalization such as need for renal replacement therapy, open chest, reoperation, and operative time, receipt of antifungal prophylaxis, and diagnosis of IFI. Multivariable Cox analysis was performed to identify risk factors of time to 1-year IFI. Results: A total of 966 heart transplant recipients were identified with a median age of 56 years (IQR 47, 62) and 72% male. 444 patients received antifungal prophylaxis which included 32% fluconazole, 34% itraconazole, 18% voriconazole, 15% echinocandin, and < 1% amphotericin or posaconazole. Over 1-year follow-up, 62 patients developed IFI with a cumulative prevalence of 6.4%. The most common organisms were Aspergillus (50%) and Candida (27%). In a multivariable model, factors associated with 1-year IFI were post-transplant renal replacement therapy (HR 3.34, 95% CI 1.69-6.60; P < 0.001) and antifungal prophylaxis (HR 0.32, 95% CI 0.11-0.96; P=0.042). Operative time, recent hospitalization, open chest, and post-transplant mechanical circulatory support were not associated with 1-year IFI. Conclusion: Renal replacement therapy after transplantation is associated with 1-year IFI. Antifungal prophylaxis appears to be protective and further prospective study is warranted to verify this finding. Disclosures: All Authors : No reported disclosures